Assessment of patient’s satisfaction regarding the service quality of a rural hospital of Burdwan district, West Bengal, India - Naskar, Prosenjit; Naskar, Somnath; Roy, Sima (International Journal Of Community Medicine And Public Health, 2017)
Background: Patients satisfaction is the basis of quality healthcare services. To improve quality of healthcare it is most important to obtain feedback from patients. Patients’ satisfaction or service quality mostly depends on patients’ expectation. This study was conducted to identify some important areas where improvement can be done by knowing patients expectation, perception and their gaps. Methods: A cross-sectional study was conducted among patients aged >18 years. Total 350 patients from OPD by consecutive sampling and 309 patients from IPD by complete enumeration was taken from a rural hospital of Burdwan district. A modified form of SERVQUAL questionnaires was used. Results: Service quality gaps were identified across all the five dimensions as well as all the 22 items of the survey instrument (except one item). All those gaps were statistically significant (Except two items). It was identified that highest service quality gap exist against the item no. 8 (Provide its services at the time) for OPD and item no. 20 (Readiness for personal attention) for IPD services. Conclusions: This study measured service quality of a hospital in the context of patients’ perceptions and expectations and identified some areas of improvement while catering health services. The findings can help the healthcare provider to plan conceptually in improving health care delivery systems.